Efek Ekstrak Kulit Mangga Arumanis (Mangifera indica L.) terhadap Paw Licking Time Mencit Putih Jantan yang Diinduksi Formalin (The Effect of Arumanis Mango (Mangifera indica L.) Peel Extract on the Paw Licking Time in White Male Mice Induced by Formalin - Rosita Sopwi Nur Lailly; Cicih Komariah; Rosita Dewi (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Mango is one of the plants which have a lot of benefits in pharmacology. Total phenol in its peel is higher than in its flesh with the main component is mangiferin and quercetin which known have activity to inhibit cyclooxygenase 2 (COX-2) enzyme. The inhibition of COX-2 leads to the decrease of the production of prostaglandin (PgE2) so it can reduce pain which marked by the decrease of paw licking time on mice induced by formalin. Formalin-induced pain is divided into two phase: early phase at 0-5th minutes and late phase at 15-30th minutes. The aim of this research was to know the effect of Arumanis mango peel extract to decrease the paw licking time in white male mice. The research design was true experimental. The result of analyses used One Way Anova shows that there were significant difference in each treatment groups with significance p < 0,05. The LSD analysis on late phase showed no significant difference between the fifth treatment group and the positive control group in LSD test. It can be concluded that arumanis mango peel extract has equal effect with natrium diclofenac in decreasing paw licking time on late phase in dosage 26 mg/g. Keywords: mango peel, paw licking time, flavonoid